Penerapan Prinsip – Prinsip Good Governance Pada Badan Usaha Milik Desa (BUMDes) di Desa Palam, Kecamatan Tinangkung Utara, Kabupaten Banggai Kepulauan - Ndina Masse; Irawaty Igirisa; Yacob Noho Nani (Transbahasa, 2025)
This study aims to analyze the accountability of the Independent Village-Owned Enterprise (BUMDes) Usaha Sinar Membangun in Palam Village, Tinangkung Utara Subdistrict, Banggai Kepulauan Regency, based on the principles of good governance. Accountability is a fundamental principle in public management and is crucial for BUMDes, which manage public resources. This research employed qualitative methods, and the data were obtained through interviews, observations, and documentation. The results indicate that the implementation of good governance principles in the management of Village-Owned Enterprises (BUMDes) has not been optimal across all aspects. Public participation is still limited, the transparency in information dissemination is not fully established, and the management accountability relies mainly on formal reports, while accountability in program governance and oversight is weak. The management's responsiveness to business issues is suboptimal, and the effectiveness and efficiency of operations are hampered due to stalled business units. The principle of justice has not been fully achieved, as the benefits of BUMDes have not been distributed equitably among the community. Additionally, law enforcement is lacking, as existing rules and regulations are not consistently followed, leading to further weaknesses in governance. Based on these findings, it can be concluded that implementing good governance principles in managing the Independent Village-Owned Enterprise (BUMDes) Usaha Sinar Membangun is underway, but not fully optimal in all aspects. Improved information transparency, a more streamlined financial accounting system, and strengthening of village regulations are needed to ensure that the BUMDes can be managed more professionally, accountably, and sustainably.